On subspace-disk transitivity of bilateral weighted shifts - Bamerni, Nareen; Kilicman, Adem (Faculty of Science, University of Malaya, 2015)
In this paper, we give some properties of subspace-disk transitive operators and use them to characterize subspace-disk transitive bilateral weighted shifts in terms of their weight sequences. As a consequence, we show that a bilateral weighted shift is subspace-disk transitive if and only if it satisﬁes the subspace-diskcyclic criterion. Then, we give a much simpler condition for some other cases.